Victimisation in the Digital Age: An Online/Offline Continuum Approach - Munk, Tine (Routledge Studies in Crime and Society Series, 2024)
Examining how victimisation can occur across the online-offline continuum while emphasising the need for a holistic approach to understanding and addressing contemporary harms, this book covers various themes of victimisation in the digital age linked to the interconnectedness and blurred boundaries between online and offline experiences.